Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Polly Getz dressed as a Las Vegas dancer and Mark Snauffer wearing black cape doing comic routine In background: Dave Maybary on saxophone and Bob Fishman on guitar